Antioxidant stress as an indicative marker of diagnosis and vector verification of treatment of generalized parodontitis with anorexia nervosa - M. Y. Antonenko; L. L. Reshetnyk; N. A. Zelinskaya; T.S. Bryuzgina (Сучасні медичні технології)
Purpose of the study. To study the balance of fatty acid spectrum of oral lipids as a marker of oxidant-antioxidant stress in patients with generalized parodontitis with anorexia nervosa.